Obesity-mediated association between exposure to brominated trihalomethanes and type II diabetes mellitus: an exploratory analysis - Andra, Syam S.; Makris, Konstantinos C.; Charisiadis, Pantelis (My University, 2014)
With the exception of chloroform, the rest of trihalomethanes (THM), the so-called brominated THM (Br-THM) are composed of bromine-substituted molecules with increased lipophilicity and potency to biological tissues. The THM are formed within disinfected tap water and their health effects, under research, range from cancer to adverse reproductive outcomes. However, the association between human exposures to Br-THM and the risk of developing type II diabetes mellitus (T2DM) and metabolic co-morbidities, such as obesity and non-alcoholic steatohepatitis has never been previously explored. The objective of this exploratory analysis was to address obesity-mediated associations between urinary concentrations of brominated THM and incidences of T2DM in a Cypriot adult population (n = 326). First morning urine voids were collected once during summer and another time during winter while a detailed questionnaire was administered to participants. Creatinine-adjusted urinary Br-THM analyte concentrations were significantly (p < 0.05) higher in T2DM cases when compared with those in healthy individuals. Multivariate logistic regression models adjusted for potential confounders showed that participants with ≥ 30 kg m− 2 BMI were at a higher T2DM risk (OR = 8.42, 95% CI: 1.97, 45.5; p < 0.01) when compared with that of normal weight participants ( < 25 kg m− 2). About 4 times higher risk for developing T2DM was observed for individuals in the upper tertile of urinary Br-THM levels (OR = 3.99, 95% CI: 1.07, 19.7; p < 0.05) when compared with the lower tertile participants. Among the participants with BMI ≥ 25 kg m− 2, urinary Br-THM levels were significantly (p < 0.001) higher in diabetics than in healthy individuals. Ingestion and non-ingestion exposures to Br-THM deserve careful consideration in relevant epidemiological studies, as a possible environmental risk factor of T2DM.
Keywords: Brominated trihalomethanes; Diabetes; Disinfection by-products; Exposure biomarkers; Obesity